(untitled) (Academicia Globe: Inderscience Research, 2024)
This article examines modern approaches to teaching journalism through the use of gamification. It analyzes the main types of gamification, their application in the educational process, as well as the advantages and challenges associated with their implementation. Special attention is given to the practical application of gamification and simulation in training journalists